2019
DOI: 10.5582/bst.2019.01339
|View full text |Cite
|
Sign up to set email alerts
|

Progress on drug pricing negotiations in China

Abstract: On November 28 th , 2019, the National Healthcare Security Administration (NHSA) and the Ministry of Human Resources and Social Security (MOHRSS) of China announced the results of drug pricing negotiations. Seventy first-negotiated drugs with 60.7% average price decrease and twenty-seven re-negotiated medicines with 26.4% average price fall, involving 11 disease categories, were successfully incorporated into National Reimbursement Drug List (NRDL). Medicines that successfully get accessed to NRDL are mostly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 2 publications
0
47
0
Order By: Relevance
“…5 To improve patient and system affordability and decrease health inequity, the Chinese government implemented a series of policies, including reimbursement-linked central medication price negotiations. 7 We found that after national medication price negotiations in 2017, procurement volumes of all pricenegotiated anticancer medications increased abruptly and significantly, except for bortezomib for which use increased initially and declined in 2018. Nonetheless, cost per DDD of all price-negotiated medication decreased between 17.3% and 78.5% by the end of the study period regardless of duration of the drugs on the Chinese market.…”
Section: Principal Findingsmentioning
confidence: 74%
See 1 more Smart Citation
“…5 To improve patient and system affordability and decrease health inequity, the Chinese government implemented a series of policies, including reimbursement-linked central medication price negotiations. 7 We found that after national medication price negotiations in 2017, procurement volumes of all pricenegotiated anticancer medications increased abruptly and significantly, except for bortezomib for which use increased initially and declined in 2018. Nonetheless, cost per DDD of all price-negotiated medication decreased between 17.3% and 78.5% by the end of the study period regardless of duration of the drugs on the Chinese market.…”
Section: Principal Findingsmentioning
confidence: 74%
“…6 All price-negotiated medications are mandated to be listed in the PRDLs. 7 Public sector hospitals must purchase these medications via the provincial procurement websites and negotiated prices are maximum prices. City or county-level insurance funding is then required to reimburse medication costs based on the negotiated prices (minus beneficiaries' copayments).…”
Section: What Do the New Findings Imply?mentioning
confidence: 99%
“…However, considering that no major adjustment was made, the impact should be minor. Finally, as China's health reform has lasted for 10 years [26], and a number of reforms have been launched, such as zero mark-up drug and drug pricing negotiations [18,27]. These policies may also have some impact on the performance indicators evaluated in our study, enlarging or distorting our research results.…”
Section: Discussionmentioning
confidence: 88%
“…However, considering that no major adjustment was made, the impact should be minor. Finally, as China’s health reform has lasted for 10 years [ 31 ], and a number of reforms have been launched, such as zero mark-up drug and drug pricing negotiations [ 18 , 32 ]. These policies may also have some impact on the performance indicators evaluated in our study, enlarging or distorting our research results.…”
Section: Discussionmentioning
confidence: 99%